2015
DOI: 10.1111/dote.12309
|View full text |Cite
|
Sign up to set email alerts
|

Primary esophageal mucosa-associated lymphoid tissue lymphoma diagnosed by using stacked forceps biopsy

Abstract: Non-Hodgkin lymphoma involving the esophagus is very rare. Only a few cases have been reported in the English literature to date, and it accounts for less than 1% of all cases of gastrointestinal lymphoma. As this malignancy manifests as a submucosal tumor, pathological diagnosis by using a simple endoscopic biopsy alone is difficult. Therefore, surgical biopsy, endoscopic mucosal resection, and endoscopic ultrasound-guided fine-needle aspiration have been used in most cases. Herein, we report a case of esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Previous studies reported one case with esophageal MALT lymphoma in stage II 2 and five cases in stage IV ( 8 , 10 , 13 , 16 , 18 , 22 ). These patients had involvement of the lung (n=2) and stomach (n=1) ( 10 , 13 ), in addition to the pharyngeal, mediastinal, intraabdominal, and pelvic lymph nodes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies reported one case with esophageal MALT lymphoma in stage II 2 and five cases in stage IV ( 8 , 10 , 13 , 16 , 18 , 22 ). These patients had involvement of the lung (n=2) and stomach (n=1) ( 10 , 13 ), in addition to the pharyngeal, mediastinal, intraabdominal, and pelvic lymph nodes.…”
Section: Discussionmentioning
confidence: 95%
“…Five cases were diagnosed after surgical resection of the esophageal tumor ( 8 , 9 , 19 , 23 , 25 ). Other procedures include endoscopic mucosal resection (n=3) ( 7 , 14 , 15 ), endoscopic ultrasound-guided fine needle aspiration (n=2) ( 13 , 16 ), a stacked forceps biopsy (n=1) ( 22 ), and endoscopic submucosal dissection (n=1) ( 21 ). Physicians can opt to use these methods when they are unable to obtain adequate specimens using a conventional biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In one case, a PR was achieved in a patient treated with rituximab monotherapy after Hp eradication (13); this was similar to the outcome in the present case. A CR was achieved in a patient treated with cyclophosphamide, vincristine, and prednisone (CVP) therapy (14), while a PR was achieved in a patient treated with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) therapy (18). Two of the four patients treated with rituximab-combined CHOP (R-CHOP) therapy achieved a CR (15-17, 19).…”
Section: Discussionmentioning
confidence: 99%
“…Deep biopsy, also known as bite-on-bite or stacked forceps biopsy, is still considered the superior choice for pathologic evaluation. [10] Alternative methods available for tissue sampling include endoscopic mucosal resection, endoscopic submucosal dissection, and submucosal tunneling with endoscopic resection. [11]…”
Section: Clinical Indicationsmentioning
confidence: 99%